Property rights and crop choice in rural Peru, 1994-2004 - Field, Alfred J.; Field, Erica Marie; Torero, Máximo (International Food Policy Research Institute, 2006)
The period of 1994 to 2004 was one in which rural households in Peru experienced dramatic changes in ownership rights through a large nation-wide land titling program and a significant opening of the economy to international trade. This paper takes this prime opportunity to examine whether lack of ownership rights presents a significant barrier to the adoption of commercial crops and/or modern farming practices as a result to changes which reduced domestic market distortions, opened up the economy and thereby presumably altered relative prices between traditional agricultural crops and those produced primarily for export. To the extent that participation was quasi-exogenous to other household features influencing production choices, the titling program serves as a natural experiment in tenure status by enabling us to compare the influence of price incentives across untitled and newly titled rural households. The econometric results confirmed that changes in these relative prices increased the likelihood that households would shift production towards these new export products. These tendencies appear to be strengthened if the household obtained title to their property over the period, which indicates that weak property institutions may inhibit the degree to which households can reap the benefits of a globalized market place. Moreover, our results indicated high returns to adoption of export products and that households which began producing an export oriented crop over the period were much less likely to be classified as impoverished in 2004. The obvious implication is that those who were unable to alter production due to reasons such as geographical location, access to credit, or lacking title to their property continued to produce traditional crops and were not able to escape poverty. This finding reaffirms the idea that liberalizing markets must be accompanied by appropriate social programs or institutional reforms directed to the unique situational problems of different subgroups in poverty if the broader poverty issue is to be improved.